RANCANG BANGUN SISTEM INFORMASI E-LEARNING PADA LP3I KRAMAT RAYA JAKARTA - Dudi Hariyadi; Ilman Manba’ullum Ramdhan (POLITEKNIK LP3I JAKARTA, 2025)
E-learning emerged as a solution to the many problems arising from limitations in time, place, and number of meetings between teachers and students. E-learning, as a tool to aid in the learning process, offers several advantages that can solve problems that often arise in the learning process. Based on the limitations in the number and time of meetings, web-based e-learning was developed using the PHP Framework Codeigniter programming language and MySQL. As a result, e-learning has been developed for LP3I Kramat Raya Jakarta with facilities as a medium for disseminating learning materials and assignments. In this e-learning application, there are three actors: admin, teacher, and student. The admin is in charge of managing the e-learning application to ensure that it runs smoothly. The admin manages data on teachers, students, and subjects. Teachers provide materials and assignments for students to complete, while students complete the assignments uploaded by teachers and study the materials uploaded by teachers. The E-Learning application supports learning activities, as schools are able to conduct learning activities beyond just teaching in the classroom. With the creation of a learning medium through the E-Learning website at LP3I Kramat Raya Jakarta, interaction between teachers and students has increased.